An Investigation in to the pracices and processes of curriculem planning and Development for General Education in Ethiopia since in 1974 - Feleke, Desta (The Ethiopian Journal of Education, 2024)
The purpuse of schoolig is to educate learners in such a way that they will be able to contribute to the walfare and strength of society .